Optimization method for main parameters of vibration protection system in motor grader seat with quasi-zero static characteristic - M. S. Korytov; I. E. Kashapova; V. S. Shcherbakov (Вестник СибАДИ)
Introduction. One of the urgent tasks facing the developers of land transport and technological machines is to reduce the vibration effects on the human operator. Vibration impacts are caused mainly by the interaction of the working bodies with the working environment and the running equipment of machines with the microrelief of the supporting surface on which the machine moves. To reduce vibration impacts, vibration protection systems of the cab and operator’s seat are used. The designs of vibration protection systems of seats with the effect of quasizero stiffness are promising. The design of a passive vibration protection system of an operator’s seat based on a parallelogram mechanism, which makes it possible to provide the specified effect of quasi-zero stiffness, is proposed. For practical application of the developed vibration protection system of a seat, it is necessary to solve the problem of assignment and optimization of its main design parameters.Materials and methods. RMS vertical acceleration of a seat in a stationary coordinate system was taken as the target function for optimizing the design parameters of the vibration protection system of a seat. For the developed calculation scheme of the seat vibration protection system based on a parallelogram mechanism, independent design parameters that influence the mean square vertical acceleration of the seat were identified. To reduce the dimensionality of the problem, some of the parameters were bound by algebraic dependencies, or fixed. The need to reduce the number of independent varying parameters was due to the relatively long simulation time of the individual process of moving the machine along the microrelief of the supporting surface using the developed complex simulation mathematical model of a motor grader with vibration-proof supports of the operator’s cabin and with a vibration-proof mechanism of the operator’s seat. The horizontal length of the parallelogram link, the ductility factor of the damper mechanism, and the horizontal dimension from the rotation axis to the limiting rollers of the mechanism were selected as independent.Results. A methodology for selecting and optimizing the design parameters of the vibration protection mechanism, presented in the form of a flowchart, which includes the stage of local optimization of the viscosity factor of the damper and the horizontal dimension from the axis to the limiting rollers by the Simplex method, has been developed. Obtaining each individual value of the target function in the local optimization was performed by processing the results of discrete values of seat acceleration obtained by simulating the movement of the machine on a simulation mathematical model. Examples of the application of the developed technique with different sets of initial data are given.Discussion and conclusions: The application of the developed technique makes it possible to unambiguously determine the values of design parameters of the vibration protection system based on the parallelogram mechanism, including geometric dimensions, the viscosity factor of the damper, as well as, as secondary output parameters, the stiffness and dimensions of the tensile spring of the mechanism.